The Sustainability of Protex and Palmolive in Singapore and Malaysia - Poh Su Ying, Racheal (2010)
The purpose of the case study is to seek for ways to produce transformative results that dramatically would change the branding of Protex and Palmolive brand in Malaysia and Singapore.